Femtosecond Laser Fabrication of Noble Metal Plasma Nanostructures and Its Application-A Mini Review - Feng, Yanshuo; Liang, Misheng; You, Rui; Li, Tianshu; Zhu, Lianqing (Frontiers in Physics, 2022)
Noble metal plasmonic nanostructures have a wide range of applications in surface-enhanced Raman scattering (SERS), solar energy conversion, optical imaging, biosensing, and many other fields due to their unique localized surface plasmon resonance effects and optical properties. In recent years, the fabrication method of noble metal plasmonic nanostructures has attracted a lot of research interest. Compared with traditional processing methods, femtosecond laser processing has the advantages of high processing resolution, small heat-affected zone, high processing flexibility, controllability, and ease of patterning, and has shown great potential for application in the fabrication method of noble metal plasmonic nanostructures. In this paper, the recent advances in the fabrication of noble metal plasmonic nanostructures by femtosecond laser are reviewed, followed by a discussion of the characteristics, advantages, and potential applications of the structures prepared by this method.